The link between tectonics and sedimentation in back‐arc basins: New genetic constraints from the analysis of the Pannonian Basin. Issue 6 (30th June 2016) - Balázs, A.; Matenco, L.; Magyar, I.; Horváth, F.; Cloetingh, S.
Abstract: The architecture of sedimentary basins reflects the relationship between accommodation space and sediment supply, their rates and localization being variable during basin evolution. The mechanisms driving the interplay between tectonics and sedimentation in extensional back‐arc basins overlying rheological weak zones inherited from an earlier orogenic evolution are less understood. A typical example is the Pannonian back‐arc basin of Central Europe. It is floored by continental lithosphere and was affected by large amounts of extension driven by the subduction rollback that took place in the Carpathians and/or Dinarides. A novel kinematic and seismic sequence stratigraphic interpretation calibrated by wells allows the quantification of the link between the formation of half grabens and coeval sedimentation in the Great Hungarian Plain part of the basin. While the lower order tectonic‐induced cycles characterize the main phases of extension in various subbasins, the higher‐order cyclicity and associated unconformities define individual moments of fault (re)activation. Our novel interpretation of a temporal and spatial migration of extension during Miocene times explains the contrasting present‐day strike of various subbasins as a result of their gradual clockwise rotation. Incorporating the observed asymmetry, in particular the associated footwall exhumation, infers that the amount of extension is much larger than previously thought. The quantitative link between tectonics and sedimentation has allowed the definition of a novel model of sedimentation in asymmetric basins that can be ported to other natural scenarios of similarly hyperextended back‐arc basins observed elsewhere. Key Points: Coupled tectonosedimentary evolution of the Pannonian Basin Kinematics of extension in back‐arc settings Migration of tectonic phases